Anemia response to Methoxy Polyethylene Glycol-Epoetin Beta (Mircera) versus Epoetin Alfa (Eprex) in patients with chronic Kidney disease on Hemodialysis - Dhayef, Alaa K; Manuti, Jawad K; Abutabiekh, Abdulwahab S (Journal of Clinical Nephrology, 2017)
Objective: Anemia, a common complication of chronic kidney disease, usually develops because of erythropoietin deficiency. Maintaining target hemoglobin (Hb) with minimal variability is a challenge in hemodialysis (HD) patients. The aim of this study is to compare the long- and short-acting erythropoietin erythropoietin stimulating agents such as Mircera and Eprex in achieving these targets. Results: The response rate in the evaluation period was higher in patients treated with methoxypolyethylene glycol-epoetin beta (Mircera) than with epoetin (Eprex) alfa: 36 of 50 (72%) mean Hb concentration (10.51g/dl) versus 29 of 50 (58%) mean Hb concentration (9.81), with statistically significant p-value <0.0001. Conclusion: Treatment with (Mircera) administered intravenously once monthly was superior to treatment with (Eprex) administered subcutaneously three times weekly for maintaining haemoglobin concentrations in patients with chronic kidney disease on hemodialysis.